Vocational and adult education in Europe - Wieringen, Fons van [Herausgeber]; Attwell, Graham [Herausgeber] (Kluwer Academic Publishers, 1999)
"The system of vocational and adult education and training in Europe offers young people and adults the opportunity to learn to play an effective part in the workplace and elsewhere in society. Vocational and adult education and training is increasingly seen as crucial to the maintenance of employment, economic growth and the social integration of disadvantaged groups. In an economy and a society which are increasingly based on knowledge and information, these tasks can only increase in importance. This book brings together contributors from different disciplines and the different countries in Europe to look at current developments and debates in the development of European education and training, including the relation between markets and institutions, learning and organisations, different programmes and sectors and the economics of education and training. The book will be of interest to students, researchers and policy makers concerned with the future of education and training in Europe." (Publisher, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Berufsbildung; Erwachsenenbildung; Weiterbildung; Lebenslanges Lernen; Beziehung Bildungssystem Beschäftigungssystem; Arbeitsmarkt; Europa; Frankreich; Schweden; Flandern